Reflections on Conversation Analytic Research in ELT - Hamid Allami; Fatemeh Mozaffari; Hossein Ali Manzouri (Research in English Language Pedagogy, 2022)
Studying L2 classroom interaction can potentially help teachers and researchers to analyze classroom discourse in order to gain insights into class-based learning and promote teachers' awareness of their teaching. To measure, analyze and describe the interaction and the behavior of participants in classrooms several approaches can be used. One of the most powerful methodologies in Applied Linguistic research and L2 classroom interactions has recently been conversation analysis. This short paper reports on several conversation analytic studies with a focus on English as a foreign language (EFL) classroom discourse and discusses the values of conversation analysis as a reflexive methodology for research on second or foreign language classroom discourse. The implications outlined are for language teaching and learning, classroom interaction, professional development of English language teachers, teacher education, and everyday talk.